Self-reconstruction through the Sense of Guilt: A Study of Select Masterpieces in the American Fiction - Mohammed Yassin Aba shaar (Universitas Muhammadiyah Gorontalo, 2020)
Abstract:Reconstruction is considered as a comprehensive transformation of one’s attitude with respect to one’s ego; one’s action; the object of guilt and the temporal-existential experience. The process of reconstruction stems from the need for improvement of the self. Any human being gets exposed to the feelings of sadness, despair, envy, shame, embarrassment and many other emotions that could leave him psychologically disabled. Anyway, guilt is a part of self-conscious emotions that the individual involves for the sake of self-evaluation. It is developed when the person feels that he doesn’t live up to the standard behaviours that are appropriate, good or correct. The feelings of guilt spur the process of reparation that reduces the consequences of negative actions. Feelings of guilt are produced as emotions of social control; they are different from one place to another depending on the culture, norms, social context and structure. This paper aims to study the feelings of guilt and their influence on self-reconstruction in three prominent, famous fictional works which are Toni Morrison’s Beloved (1987), Khalid Hosseni’s The Kite Runner (2003) and Nathenial Hawthorn’s The Scarlet Letter (1850). It is going to inspect how the feelings of guilt foster the development of a stable trend towards order and improvement.